Breakeven price of biomass from switchgrass, big bluestem, and Indiangrass in a dual-purpose production system in Tennessee. (December 2015) - Boyer, Christopher N.; Griffith, Andrew P.; McIntosh, David W.; Bates, Gary E.; Keyser, Patrick D.; English, Burton C.
Abstract: The objective was to determine the breakeven price for switchgrass (SG) ( Panicum virgatum L.), a mix of big bluestem ( Andropogon gerardii Vitman) and Indiangrass (BBIG) ( Sorghastrum nutans L. Nash), and a combination of SG and BBIG (SG/BBIG) produced under three harvest treatments. Two-harvest treatments included a forage harvest at early boot (EB) and at early seedhead (ESH) plus a biomass harvest at fall dormancy (FD). The third harvest treatment was a single biomass harvest at FD. Mixed models were used to determine if there were differences in yield, crude protein, and nutrient removal for each of the native warm-season grass (NWSG) treatments at each harvest. The EB plus FD harvest system would be preferred over the ESH plus FD harvest system for all NWSG treatments. BBIG was the only NWSG treatment with a breakeven price for biomass that decreased with an EB harvest. For all three NWSG treatments, a producer would be better off harvesting once a year for biomass than twice for forage and biomass. The cost of harvesting and replacing the nutrients for the forage harvest was greater than the revenue received from selling the forage. Highlights: Yield was highest for switchgrass. Crude protein decreased from the early boot to the early seedhead harvest. Single-harvest production is more profitable than dual-purpose biomass production. Single-harvest of switchgrass was the more economically viable bioenergy crop.